Dinamika Wacana Pluralisme Keagamaan di Indonesia - Sanuri, Sanuri (Religió: Jurnal Studi Agama-agama, 2012)
Religious plurality in Indonesia context is interesting enough to be discussed. The plurality of culture, race, ethnic and religion constitutes a social condition that often becomes disintegrated major. Pluralism in the context of religion such as Islam has a pivotal role in dealing with such issue. In Islam, all religions and beliefs are believed to have the right of life. But for a certain group, this matter is considered as a faith destruction of Muslim. This article discusses the response from both internal and external groups of Islam concerning with the understanding of Islam to religious pluralism which is currently considered as a trend of globalization and modernization—apparently raises ideological suspicions or even new ideologies. Therefore, an effort to re-actualization of meanings and values into the frame of Islamization, SIPILIS (secularism, pluralism and liberalism) in Indonesian context is necessary. In addition, re-interpretation of the term “religious pluralism” will be more oriented to an attempt to search mutual understanding of different cultures, religions, races and tribes. In this context, the social construction method and socio-historical, moral ethics, and theological-philosophical approach under the central issues within a religious pluralism spectrum such as global theology, universal theology, universal friendship, culminated tradition, private faith, relative truth, the real, relative truth, universality and Humanism of Islam are very essential.